Chiasmus: the state of the art: includes papers from the Chiasmus Jubilee Conference at BYU, August 15-16, 2017 - Welch, John W.; Parry, Donald W. (BYU studies quarterly, 2020)
Introduction / Donald W. Parry and John W. Welch -- Chiasmus in the Book of Genesis / Gary A. Rendsburg -- Chiastic structuring of the Genesis flood Story : the art of using chiasm as an effective compositional tool for combining earlier chiastic narratives / Steven R. Scott -- Exegesis or eisegesis : does chiastic analysis help us to understand Leviticus 20? / Jonathan Burnside -- At the intersection of scribal training and theological profundity : chiasm as an editorial technique in the primeval history and Deuteronomy / Bernard M. Levinson -- Chiasmus in the text of Isaiah : MT Isaiah versus the great Isaiah scroll (1QIsaa) / Donald W. Parry -- "With strong hand and with outstretched arm" (Deuteronomy 4:34), "With outstretched hand and with strong arm" (Jeremiah 21:5) : chiasmus in Deuteronomy and Jeremiah / David Rolph Seely -- Narrating homicide chiastically / John W. Welch -- Chiastic structuring of large texts : 2 Nephi as a case study / Noel B. Reynolds -- Jesus and the Roman Centurion (Matthew 8:5--13) : a window to chiasmus and apostolic pedagogy / H. Douglas Buckwalter -- Rethinking the structure of the "farewell discourse" (John 13-17) through a chiastic lens / Wayne Brouwer -- From "linguistic turn" and Hebrews scholarship to anadiplosis iterata : the enigma of a structure / Gabriella Gelardini -- Mirrored poeticity : chiastic structuring in Mayan languages / Kerry Hull -- Chiasmus criteria in review / Neal Rappleye -- Truth or cherry picking : a statistical approach to chiastic intentionality / Boyd F. Edwards and W. Farrell Edwards -- The roles of words, phrases, and ideas in macro-chiasms / Stephen Kent Ehat.